2010
DOI: 10.1097/brs.0b013e3181b71bd1
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Months Follow-up in Forty-Nine Patients With Acute/Semiacute Osteoporotic Vertebral Fractures Treated Conservatively or With Percutaneous Vertebroplasty

Abstract: PVP is a good treatment for some patients with acute/subacute painful osteoporotic vertebral fractures, but the majority of fractures will heal after 8 to 12 weeks of conservative treatment with subsequent decline in pain. The risk of new fractures needs further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
193
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(196 citation statements)
references
References 19 publications
2
193
0
1
Order By: Relevance
“…Included Articles N=27 of the studies reported effects for the same group of patients and were combined into one analyzable ''study'' (Kasperk/Grafe et al, 4 total [11,12,24,25] and Rousing et al, 2 total [20,26]; see Table 1). This systematic review was reported in accordance with the PRISMA statement [27].…”
Section: Bkp Vs Nsm N=6mentioning
confidence: 99%
“…Included Articles N=27 of the studies reported effects for the same group of patients and were combined into one analyzable ''study'' (Kasperk/Grafe et al, 4 total [11,12,24,25] and Rousing et al, 2 total [20,26]; see Table 1). This systematic review was reported in accordance with the PRISMA statement [27].…”
Section: Bkp Vs Nsm N=6mentioning
confidence: 99%
“…Rousing et al 28 accompanied 49 patients with acute (less than two weeks) and subacute (between two and eight weeks) fractures from osteoporosis, 25 of whom had undergone PV and 24 of whom had undergone a non-surgical procedure, over a 12-month period, in a randomized clinical study. Pain was evaluated using a visual analog scale.…”
Section: A B Resultsmentioning
confidence: 99%
“…However, there is still a lack of consensus regarding the clinical longterm efficacy and superiority of this technique in comparison with conservative treatment [1][2][3][4][5][6][7][8][9]. Reported complications, possibly due to the addition of a material that is stiffer than the surrounding bone, include fractures of the augmented and adjacent vertebrae.…”
Section: Introductionmentioning
confidence: 99%
“…New osteoporotic vertebral compression fractures, in the months after VP, are reported in 7-63 % of VP patients, up to 82 % of these occur at the adjacent levels, with adjacent fractures occurring sooner than nonadjacent fractures; rates of recurrent fracture of the augmented vertebra itself range up to 63 % in the literature [1,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It is still under debate whether new vertebral fractures appear more often in patients who received cement augmentation than in conservatively treated patients; some studies support this hypothesis [1,6,7,[27][28][29], while others question it [2,3,26,30]. Reducing the augmentation volume [31], using low-modulus PMMA [32] and prophylactic augmentation of adjacent vertebrae [13,25,33] have been proposed as ways of minimizing the risk of subsequent fractures.…”
Section: Introductionmentioning
confidence: 99%